Inventory Management Practices of Small-Scale Pharmacies in the Selected Towns in Cavite: A Marketing Perspective - Venice Lara Soliveres; Aidie Herrera; Alyannah Kathlyn Cedillo (Research Synergy Press, 2024)
Effective inventory management is crucial for pharmacies because it guarantees the consistent availability of pharmaceutical products and minimizes the risk of stickouts or overstock situations, thereby enhancing customer satisfaction. This study aimed to determine the inventory management practices of small-scale pharmacies in selected towns in Cavite, Philippines. The researchers employed descriptive research and a purposive sampling technique. This study used 50 legally registered small-scale pharmacies. The findings revealed that most of the participants were under sole proprietorship with one to nine employees and estimated assets of P3,000,000 and below and have been in operation for one to three years and ten years and above. Furthermore, the predominant inventory management practice in terms of sourcing is Economic Order Quantity (EOQ). Fast Moving, Slow Moving, Non-Moving (FSN) Analysis, and First Expiry, First Out (FEFO) are common storage methods. Moreover, First Expiry, First Out (FEFO) is frequently utilized in selling. This study may provide related, timely information, analysis, and results that may serve as a foundation for the business to grasp on what to continue, enhance, and implement in their inventory management practice, which might also contribute to the efficient and effective movement of products and to cater to the needs of the customers. Thus, the researchers recommended modifying the existing inventory management practices employed in sourcing, storing, and selling. This adaptation aims to effectively monitor and control the movement of inventories from the moment of acquisition to the moment of transaction.